2018
DOI: 10.1038/s41396-018-0169-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and interactions of highly resolved marine plankton via automated high-frequency sampling

Abstract: Short timescale observations are valuable for understanding microbial ecological processes. We assessed dynamics in relative abundance and potential activities by sequencing the small sub-unit ribosomal RNA gene (rRNA gene) and rRNA molecules (rRNA) of Bacteria, Archaea, and Eukaryota once to twice daily between March 2014 and May 2014 from the surface ocean off Catalina Island, California. Typically Ostreococcus, Braarudosphaera, Teleaulax, and Synechococcus dominated phytoplankton sequences (including chloro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 78 publications
8
67
0
Order By: Relevance
“…Despite the relatively low observed growth rates (0.19-0.44 per day), all three MGII MAGs had predicted maximum growth rates based on CUB near or over 2 per day. This suggests that MGII may be quite active in certain environments, as we previously reported for SPOT where MGII 16S rRNA sequences comprised over 40% of the microbial community (higher than SAR11) on one post-spring-bloom day [56]. Further, MGII have also been found to be very abundant in Monterey Bay, CA [57] and the Northern Gulf of Mexico "Dead Zone", where they were found to be over 10% of the total microbial community [45].…”
Section: Bacterial Growth Rates Of Uncultivated Cladessupporting
confidence: 72%
“…Despite the relatively low observed growth rates (0.19-0.44 per day), all three MGII MAGs had predicted maximum growth rates based on CUB near or over 2 per day. This suggests that MGII may be quite active in certain environments, as we previously reported for SPOT where MGII 16S rRNA sequences comprised over 40% of the microbial community (higher than SAR11) on one post-spring-bloom day [56]. Further, MGII have also been found to be very abundant in Monterey Bay, CA [57] and the Northern Gulf of Mexico "Dead Zone", where they were found to be over 10% of the total microbial community [45].…”
Section: Bacterial Growth Rates Of Uncultivated Cladessupporting
confidence: 72%
“…Finally, at the site level, emerging molecular methods will bring major insights by identifying important microbial actors, determining their interactions, and providing deeper insights into biogeochemical processes at ILTER sites. One example of this technology is the MBARI Environmental Sample Processor (Scholin et al, 2009), which has been used to autonomously collect and preserve microbial samples (Ottesen et al, 2011), revealing complex shifts in microbial communities over very short time scales (Needham et al, 2018). See McQuillan and Robidart (2017) for a comprehensive review of recent advances.…”
Section: Site Levelmentioning
confidence: 99%
“…More recently, Needham and Fuhrman looked at the succession of phytoplankton, archaea and bacteria, but only during 6 months [30]. Another study in the same ecosystem, relying on automated sampling, showed daily and highly dynamic population variations in the three domains of life, and extensively described the biological interactions that took place during the sampling period [56]. A study looking at bacterioplankton diversity and phytoplankton microscopy counts, has shown that despite interannual variations in phytoplankton blooms, bacterioplankton microdiversity patterns seem stable in both bloom and non-bloom conditions [57].…”
Section: Discussionmentioning
confidence: 99%